Enantioselective Organ Catalytic Synthesis of Chiral Spirooxindoles via One-Pot Cascade Reactions: A Greener Strategy for Drug-Like Molecules - Aishwarya Patel; Dr. Kamalesh Kumar Patel (International Journal of Scientific Research in Chemistry, 2025)
The development of efficient and sustainable synthetic methodologies for constructing stereochemically rich scaffolds remains a central focus in modern organic chemistry. In this study, we report a green and highly enantioselective organocatalytic one-pot cascade reaction for the synthesis of chiral spirooxindoles—scaffolds of significant pharmacological interest. The reaction sequence involves a Michael addition, followed by a Mannich-type reaction and intramolecular cyclization, catalyzed by a bifunctional squaramide-based organocatalyst under mild conditions in ethanol, a green solvent. Through systematic optimization, we identified squaramide–quinine as the most efficient catalyst, affording excellent yields (up to 89%), high enantioselectivities (up to 93% ee), and complete diastereocontrol (>20:1 dr). The reaction demonstrated broad substrate compatibility with various N-substituted isatins and nitroalkenes, enabling the synthesis of a diverse set of spirooxindole derivatives. Structural characterization was confirmed by NMR, HRMS, and X-ray crystallography. In silico ADME studies indicated favorable drug-likeness profiles, with all compounds satisfying Lipinski's rule of five. Furthermore, the protocol aligns with green chemistry principles, exhibiting excellent atom economy (83.4%) and a low E-factor (2.7). The one-pot cascade nature minimizes purification steps, reduces waste, and enhances synthetic efficiency. This study offers a practical, scalable, and environmentally responsible method for accessing biologically relevant spirooxindoles, paving the way for future applications in medicinal chemistry and drug discovery.
Keywords: Chiral spirooxindoles; Organocatalysis; One-pot cascade reaction; Green chemistry; Enantioselective synthesis; Squaramide catalysts; Drug-likeness; Sustainable synthesis